AN ANALYSIS ON THE STUDENTS’ SPEAKING PERFORMANCE IN GIVING PRESENTATION - Aminullah, Fajar; Apriliaswati, Rahayu; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract : this study is conducted to analyze the students? speaking performance in giving presentation. The technique used in this research is direct technique with direct observation of behavior. Tools of data collecting used are rubric, observation sheet and video recorder. The method applied is descriptive study. Based on the observation result, the data of content aspect showed that 16 students (64%) get ? 2 score, 7 students (28%) get score between 2.1 ? 2.5, and only 2 students (8%) get score ? 2.6. Then from the result, the data of delivery aspect showed that 11 students (44%) get score between 2.1 ? 2.5, 10 students (40%) get score ? 2, and 4 students (8%) get score ? 2.6. Based on those result, it can be concluded that the third semester students of English Education Study Program of FKIP Untan Pontianak in academic year 2014/ 2015 especially the students who were in Class B of Speaking for Academic Presentation have moderate abilities of speaking performance in giving presentation. Keywords : Speaking Performance, Presentation Abstrak : Penelitian ini dilakukan untuk menganalisis kemampuan siswa dalam memberikan presentasi. Teknik yang digunakan dalam penelitian ini adalah teknik langsung dengan pengamatan perilaku langsung. Alat pengumpulan data yang digunakan adalah rubric, lembar observasi dan perekam video. Metode yang digunakan adalah penelitian deskriptif. Berdasarkan hasil pengamatan, dapat disimpulkan bahwa hasil penilaian berdasarkan muatan presentasi yaitu 16 siswa (64%) mendapatkan skor ? 2, 7 siswa (28%) mendapat skor antara 2.1 ? 2.5, dan hanya 2 siswa (8%) mendapatkan skor ? 2.6. kemudian hasil penilaian berdasarkan penyampaian yaitu 11 siswa (44%) mendapat skor diantara 2.1 ? 2.5, 10 siswa (40%) mendapat skor ? 2, dan 4 siswa mendapat skor (8%) mendapat skor ? 2.6. Berdasarkan hasil tersebut, dapat disimpulkan bahwa mahasiswa semester III Pendidikan Bahasa Inggris FKIP Untan Program Studi Pontianak pada tahun akademik 2014/ 2015 terutama siswa yang berada di kelas B Berbicara dalam Presentasi Akademik memiliki kemampuan moderat. Kata Kunci : Kemampuan Berbicara, Presentasi